Ear Acupuncture Points in Neonates From Drug-Dependent Mothers: A Prospective Study - Kirsten Stähler van Amerongen; Annette Kuhn; Daniel Surbek; Mathias Nelle (Frontiers Media S.A., 2021)
Aim: The aim of the study was to determine the presence or absence of ear acupuncture points (EAP) in newborn children with or without neonatal abstinence syndrome (NAS) and to confirm the hypothesis that neonates with NAS have more EAP than healthy neonates.Methods: We conducted a prospective case control study with ethical consent at the University Children's Hospital, Division of Neonatology Bern and the Department of Gynecology and Obstetrics Inselspital Bern in Switzerland. We determined the EAP in n = 26 newborn children born to drug-dependent mothers compared with n = 50 healthy newborns. For the detection of EAP, we used an ear point detection pen. EAP are present only if weakness exists in the corresponding area.Results: Twenty-six neonates who were born to drug-dependent mothers and developed NAS were screened on the 5th day after delivery (range 1-22). The median Finnegan Score was 12 points (range 6-18) on the day of examination. Twenty-four active EAP were detected on the left earlobe and 25 were detected on the right earlobe. There was no significant difference between the right and left lobes (p = 0.9285, two tailed test) and the number of acupuncture points. The correlation between the Finnegan Score and the number of EAP was highly significant (p = 0.0001). The most common active points were the psycho-vegetative rim of the reflex zone of sympathicus and parasympathicus. Organic points were also commonly detected. The urinary bladder, kidney and hip points were detected with a frequency of 12-15%. The shen men pain point was found in three neonates, and the point of desire as a psychological point, was also detected. The correlation between sex and active EAP was highly significant (p = 0.0093, Mann-Whitney test for the left earlobe and p = 0.0025 for the right earlobe). Boys had a significantly higher number of EAP than girls. All NADA points were detected in the neonates born to drug-dependent mothers, and the most frequent point was the vegetative point. Healthy neonates showed only the vegetative point in the vegetative rim 1/3 among the NADA points. A comparison of newborns born to drug-dependent mothers and 50 healthy neonates showed that the former group had statistically significantly more active points. For the left earlobe, the difference between neonates born to drug-dependent mothers and controls was statistically significant (p = 0.0008, Mann-Whitney test). Highly similar results were found for the right earlobe (p = 0.0001, Mann-Whitney test).Discussion: Our current work confirms that neonates born to drug-dependent mothers with high Finnegan scores and NAS have more EAP than healthy neonates. The vegetative rim is the most common point as shown in our previous studies. Our observations showed that twins had similar but not identical points; each individual had unique points depending on health status. Newborn boys with NAS had a higher number of EAP than newborn girls in the neonatal intensive care unit. This findings may be attributed to the reserve of newborns with NAS. Newborn girls are considered more robust than boys in the neonatal care setting. EAP in neonates might potentially be used for diagnosis and therapeutic opinions in neonates in the future.